Hydrogen incorporation in diamond: the nitrogen-vacancy-hydrogen complex. - Glover, C; Newton, M; Martineau, P; Twitchen, D; Baker, M (2003)
We report the identification of the nitrogen-vacancy-hydrogen complex in a freestanding nitrogen-doped isotopically engineered single crystal diamond synthesized by chemical vapor deposition. The hydrogen atom is located in the vacancy of a nearest-neighbor nitrogen-vacancy defect and appears to be bonded to the nitrogen atom maintaining the trigonal symmetry of the center. The defect is observed by electron paramagnetic resonance in the negative charge state in samples containing a suitable electron donor (e.g., substitutional nitrogen N(0)(S)).